Touching the Qur'an for Menstruating Women Perspectives of Imam An-Nawawi and Imam Ibn Hazm: a Case Study of the Tahfiz Al-Faiz Islamic Boarding School - Zakwani, Rif’ah; Marpaung, Arifin (Journal of Public Representative and Society Provision, 2024)
This study aims to examine the views of Imam An-Nawawi and Imam Ibn Hazm regarding the permissibility of touching the Qur'an for women who are menstruating (haid), with a focus on its implementation at Pondok Pesantren (Islamic Boarding School) Tahfiz Al-Faiz in Deliserdang Regency. The study analyzes the differing opinions of these two scholars on the issue. Imam An-Nawawi, in his al-Majmu', holds the view that menstruating women are not allowed to touch the Qur'an directly. In contrast, Imam Ibn Hazm, in al-Muhalla, argues that there is no prohibition against touching the Qur'an during menstruation, as there is no authentic hadith to support such a ban. This research employs a qualitative approach with a case study at Ponpes Tahfiz Al-Faiz, involving interviews with the administrators and students to understand the practices followed in the institution. The findings reveal that the majority of the administrators and students adhere to Imam An-Nawawi's opinion, although some are inclined to follow Imam Ibn Hazm's view, depending on their understanding and the approach practiced in their environment. This study is expected to contribute to the development of a more inclusive and contextually relevant understanding of Islamic jurisprudence in the context of religious education in Islamic boarding schools.